The Influence of Self Regulated Learning to Mathematics Critical Thinking Ability on 3D-Shapes Geometry Learning using Geogebra - Hidayati, Destia Wahyu; Kurniati, Lenny (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2018)
3D-Shapes Geometry is one of the subjects material that must be taught to students in Mathematics Education Program, which later after graduation will become a math teacher. Learning 3D-Shapes Geometry has relevance to the mathematics critical thinking ability. Students who have the ability to think critically can think rationally by collecting information as completely as possible. Learning that can stimulate the ability of critical thinking should be learning in which there are activities that are student-centered learning. One of the lessons in 3D-Shapes Geometry that can be used is learning using Geogebra Software . Learning 3D-Shapes Geometry using GeoGebra aided is very possible to make students practice independently spatial capabilities that will foster self regulated learning. The existence of self-regulated learning in the student's learning will make the students able to interpret, analyze, evaluate, and infer in learning. These capabilities will form the mathematics critical thinking ability. The purpose of this research is to determine whether or not there is a relationship between self regulated learning and mathematics critical thinking ability and to find out coefficient of correlation of them. This research is a quantitative research. Before the research begins, the researchers took the value of the task as the preliminary data and it is tested normality. Data collection techniques in this research is the scale of self regulated learning and tests in the form of mathematics critical thinking ability. The scale of self regulated learning and mathematics critical thinking ability tests are validated first. Data test of mathematics critical thinking ability of is tested normality, then data of scale self regulated learning and test of mathematics critical thinking ability are tested regression. The result of this research is there is influence of self regulated learning to the mathematics critical thinking ability of 45 , 7 %.